2018
DOI: 10.1111/vru.12673
|View full text |Cite
|
Sign up to set email alerts
|

Extruded gallbladder mucoceles have characteristic ultrasonographic features and extensive migratory capacity in dogs

Abstract: Limited information is available on the ultrasonographic characteristics of extruded gallbladder mucoceles. The objective of this retrospective case series study was to describe the ultrasonographic features of extruded gallbladder mucoceles in a group of dogs. Medical records of four veterinary centers were searched between June 2010 and January 2018 for all dogs with a suspected extruded gallbladder mucocele based on abdominal ultrasound. Seven client-owned dogs met the inclusion criteria. All seven dogs had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Extension of gelatinous bile into the cystic duct, common bile duct (CBD), and hepatic ducts may occur, causing varying degrees of extrahepatic biliary obstruction (EHBO). 1,2,5,6,11 The etiology of GBM is incompletely understood but thought to be multifactorial. 1,12,13 Gallbladder dysmotility may result in functional obstruction of the cystic duct and CBD, or mechanical obstruction of the ducts by mucus, choledocholithiasis, or pancreatitis may cause bile stasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Extension of gelatinous bile into the cystic duct, common bile duct (CBD), and hepatic ducts may occur, causing varying degrees of extrahepatic biliary obstruction (EHBO). 1,2,5,6,11 The etiology of GBM is incompletely understood but thought to be multifactorial. 1,12,13 Gallbladder dysmotility may result in functional obstruction of the cystic duct and CBD, or mechanical obstruction of the ducts by mucus, choledocholithiasis, or pancreatitis may cause bile stasis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,17,18 Increased mucus secretion occurs, and, in some cases, cystic mucinous hyperplasia of the GB. 1,2,6,9,10,12,[17][18][19][20][21] Fibrinosuppurative and necrotizing, hemorrhagic cholecystitis may develop with GBM and cause transmural ischemia and GB rupture. 2,5,17,19,20,22 Cholecystectomy addresses the defective GB wall and is the most appropriate treatment for GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Cocker spaniels, miniature schnauzers, and Shetland sheepdogs appear particularly prone to gallbladder mucocele development and a hereditary component is considered in these breeds . Recent research has also shown the migratory capacity of extruded gallbladder mucoceles in the abdomen as identified on abdominal ultrasound . Although mucoceles are readily detected using ultrasonography, relative to CT, it can result in longer scan times, greater patient discomfort from physical compression of the ultrasound probe, and incomplete evaluation of the abdomen in large patients .…”
Section: Introductionmentioning
confidence: 99%
“…9,[15][16][17][18] Recent research has also shown the migratory capacity of extruded gallbladder mucoceles in the abdomen as identified on abdominal ultrasound. 19 Although mucoceles are readily detected using ultrasonography, relative to CT, it can result in longer scan times, greater patient discomfort from physical compression of the ultrasound probe, and incomplete evaluation of the abdomen in large patients. 20 Thus, CT could allow faster and more complete abdominal evaluation for these patients, but scientific investigation of canine biliary contents in veterinary medicine using CT is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…All patients that were included had either a necropsy, surgery, or fluid analysis confirmation performed in order to prove or disprove gallbladder rupture. Rupture of the gallbladder was considered if a full thickness defect in the gallbladder wall on surgery or histopathology, if the gallbladder was adhered to the surrounding tissues at surgery, if fibrosis of a previous area of gallbladder wall rupture was found on histopathology, if abdominal effusion contained bilirubin granules, 10 cytologically, or if a mucocele was found in any other location except the gallbladder 19 . Lack of these findings was considered to be nonperforated cases.…”
Section: Methodsmentioning
confidence: 99%